A systematic review and meta-analysis of Tobacco 21 policies and youth tobacco use: implications for future policy researchResearch in context - Danyi Li; Shiyou Wu; Steve Sussman; Mary Ann Pentz (The Lancet Regional Health. Americas)
Summary: Background: Raising the sales age to 21 is among the most important steps to curb tobacco/nicotine use in youth in the past two decades. The study aims to systematically review and perform meta-analyses on the impact of Tobacco 21 (T21) policies on tobacco use among 11-to-20-year-olds in the United States, encompassing T21s at local, state, and national levels. Methods: We screened 14 databases following PRISMA and PICOS criteria, applying standardized abstraction forms and quality assessment tools. Inverse-variance-weighted random-effects models estimated pooled, fully adjusted odds ratios (ORs) for tobacco use outcomes, with moderation analyses by T21-level, gender, age, and race/ethnicity proportions. Sensitivity analyses considering study quality and study-level clusters were conducted. Findings: Among 24 studies included, T21s were associated with current cigarette (OR = 0.92, 95% CI: 0.77–1.11), chewing tobacco (OR = 0.89, 95% CI: 0.65–1.23), e-cigarette (OR = 1.32, 95% CI: 0.88–1.97), and cigar/cigarillo use (OR = 0.98, 95% CI: 0.55–1.73) compared to non-T21 areas and pre-T21 periods. Moderation analyses showed that studies on the Federal T21 and studies with fewer female participants (<50%) had significantly lower odds of cigarette use; No significant moderation effects by race/ethnicity or age-group. Interpretation: Almost all meta-analyses had null findings, suggesting null policy effects on reducing the prevalence of youth tobacco use. There is evidence that the policy level and gender proportion in studies moderated T21 effects. Future research and practice should consider policy levels, youth age ranges, analytic strategies, and implementation factors such as ID verification and compliance check inspections that may improve T21's effectiveness in reducing youth tobacco use. Funding: No funding.